The Omnipresence of Judgment and Absent “Justice”: Disjunctions in the Art in Medieval Catalonia - Alcoy, Rosa (Eikón / Imago, 2023)
The imago of Justice has attracted attention since ancient times and, in the most recent period, the approaches to the subject have multiplied. The question that arises here is not about the image of Virtue itself, although it is valued and taken into account, to point out its unity without forgetting the fickle aspects of its alleged monolithic configuration, capable of generating important changes in its iconic appearance. The study concentrates on the revision of its absences in medieval Catalan art. To describe and analyse these hollow spaces that make us think of a denial of Justice –understood in its feminine personification– I examine their repeated or sporadic presence in different places of Europe while approaching those that were their alternatives in Catalan religious and civil contexts. This cessation in its functions should not have been conditioned only by a lack of knowledge and, in any case, could be the result of a disjunctive graphic thinking that prioritizes other issues and motives when it comes to representing the idea of judgment or justice.